Integrity management in onshore facilities with 3D high definition survey (hds) technology (2017)
Introduction: This article derives from the research “Integrity management in onshore facilities with 3D high definition survey (hds) technology” by the Universidad Pedagógica y Tecnológica de Colombia, conducted during 2016 and 2017. Methodology: We started from a documentary review of ScienceDirect, Proquest, ebsco, and dialnet; the general factors of an SGI were established; the validation of 3dhds, and its incorporation into the integrity and benefit management system are presented. Results: A technology integration methodology based on the laser modeling of the actual status of assets in “as-built” or “as-is” phases is introduced in order to have a more real vision of the state, presenting the case study of the methodology used by Inspectra srl (Bolivia). Conclusion: Despite the little use of this technology in facilities, we could observe its capacity to produce integrity results such as reverse engineering support, in-service inspections, aptitude for service, and as a tool to control management of change (moc), among others, and thus make decisions on how to manage them using location data, and real dimensions.